Incomparable Poetry An Essay on the Financial Crisis of 2007-2008 and Irish Literature - Kiely, Robert (Robert Martin) (Punctum Books, 2020)
Incomparable Poetry: An Essay on the Financial Crisis of 2007-2008 and Irish Literature is an attempt to describe the ways in which the financial crisis of 2007-8 impacted literature in Ireland, and thereby describe the ways in which poetry engages with, is structured by, and wrestles with economic issues.Ireland and its contemporary poetry is a particularly suitable case study for studying the effect of the economic crisis on Anglophone poetry, because poetry in Ireland has a special relationship to the state and economy due to its status as a postcolonial nation-state. Beginning with a summary of recent Irish economic and cultural history, and moving across experimental and mainstream poetry, this essay outlines how the poetry of Trevor Joyce, Leontia Flynn, Dave Lordan, and Rachel Warriner addresses in its form and content the boom years of the Celtic Tiger and the financial crisis.Incomparable Poetry also discusses the concerns and historical contexts these poets have turned to in order to make sense of these events - including Chinese history, accountancy, sexual violence, and Iceland's economic history. In contemporary Irish poetry, the author argues, we see a significant interest in matching capitalism's accounting abilities, but in this attempt, these poems often end up broken by the imposition of an external conceptual framework or economic logic.